ANALISIS PENERAPAN AKUNTANSI SYARIAH SISTEM BAGI HASIL DALAM PROGRAM TABUNGAN PADA BANK SYARIAH MANDIRI CABANG GRESIK - PUTRA, ADITYASMONO (Jurnal Akuntansi AKUNESA, 2012)
This study aims to analyze the application of Islamic accounting in Gresik City Bank Syariah Mandiri. The method used is descriptive method is to compare the application of the object of research with existing theories and then drawn a conclusion. These results indicate that the application of accounting in the Islamic Syariah Mandiri Bank is well in accordance with the principles of Islamic Accounting. Bank Syariah Mandiri apply the principle of mudharabah muthlaqah in the BSM savings program. While in principle sharing for Bank Syariah Mandiri using the method of revenue sharing. The application of Islamic Accounting in the calculation of sharing at Bank Syariah Mandiri is in appropriate with his theory with the same results in a monthly report Income Distribution. Keywords: Islamic Accounting, sharing system, savings